Genomic epidemiology of Group B Streptococcus colonization among pregnant women in Japan, 2021–2023 - Chizu Nishi; Hirofumi Ohtaki; Masaki Karino; Hiromi Uekita; Ayumi Sano; Tetsuya Kobayashi; Susumu Kaino; Yoshiki Sakamoto; Satoshi Nakano (PLoS ONE, 2026)
Group B Streptococcus (GBS) colonization in pregnant women is a major risk factor for neonatal diseases; however, molecular epidemiological studies on GBS in Japan remain limited. We characterized 219 GBS isolates recovered from vaginal screening cultures at a general hospital in Osaka Prefecture, Japan between 2021 and 2023. Capsular type, clonal complex/sequence type (CC/ST), virulence factors (pilus islands, Alp family, Srr1/Srr2, and HvgA), and antimicrobial resistance determinants were analyzed using whole-genome sequencing. The predominant lineages were CC19 (27.9%), CC23 (21.9%), and CC1 (21.0%), whereas the hypervirulent CC17 lineage accounted for only 5.5% of isolates. Capsular type Ia, III, and V comprised >60% of the isolates. PI-1/PI-2a (58.0%) was the predominant pilus profile, and rib (35.2%) was the most frequent Alp family gene. The hypervirulence-associated markers hvgA and srr2 were confined to capsular types III/CC17 and IV/CC452. All isolates were susceptible to β-lactams and vancomycin, whereas resistance to macrolides, clindamycin, and levofloxacin was observed at varying frequencies. These findings provide a pre-vaccine molecular baseline for maternal GBS carriage in Japan and highlight srr2 -positive CC452 as a potential emerging lineage of concern.